2013
DOI: 10.1128/mcb.00418-13
|View full text |Cite
|
Sign up to set email alerts
|

Smurf1-Mediated Lys29-Linked Nonproteolytic Polyubiquitination of Axin Negatively Regulates Wnt/β-Catenin Signaling

Abstract: Ubiquitination plays important and diverse roles in modulating protein functions. As a C2-WW-HECT-type ubiquitin ligase, Smad ubiquitination regulatory factor 1 (Smurf1) commonly serves to regulate ubiquitin-dependent protein degradation in a number of signaling pathways. Here, we report a novel function of Smurf1 in regulating Wnt/␤-catenin signaling through targeting axin for nonproteolytic ubiquitination. Our data unambiguously demonstrate that Smurf1 ubiquitinates axin through Lys 29 (K29)-linked polyubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 41 publications
3
86
0
Order By: Relevance
“…Our previous study has demonstrated that Smurf1 ubiquitinates Axin through K29-linked poly-ubiquitination, which interrupts Axin-LRP5/6 association and then inhibits Wnt/␤-catenin signaling (14). In the present work, we showed that the C2 domain of Smurf1 was crucial for its interaction with Axin, suggesting a non-canonical WW-PY-independent interaction for the two proteins.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Our previous study has demonstrated that Smurf1 ubiquitinates Axin through K29-linked poly-ubiquitination, which interrupts Axin-LRP5/6 association and then inhibits Wnt/␤-catenin signaling (14). In the present work, we showed that the C2 domain of Smurf1 was crucial for its interaction with Axin, suggesting a non-canonical WW-PY-independent interaction for the two proteins.…”
supporting
confidence: 55%
“…Point mutations of Axin and Smurf1 were generated using a Stratagene QuikChange site-directed mutagenesis kit. Other plasmids have been applied previously (14). Specific siRNA oligos against human Smurf1 and Axin were synthesized in Genepharma.…”
Section: Methodsmentioning
confidence: 99%
“…Wnt ligands lead to inactivation of this destruction complex, allowing β-catenin to accumulate, translocate to the nucleus, and, together with its partner TCF/LEF-family member, activate a transcriptional program (Clevers and Nusse, 2012). Recently, the ubiquitin E3 ligase Smad ubiquitylation regulatory factor 1 (Smurf1) has been shown to modify Axin with nondegradable K29-linked ubiquitin polymers (Fei et al, 2013). K29-polyubiquitylation of Axin disrupts its interaction with the Wnt coreceptors LRP5 and LRP6 (LRP5/6), which subsequently attenuates Wnt-stimulated LRP6 phosphorylation and represses Wnt/β-catenin signaling (Fei et al, 2013).…”
Section: K29 Linkages -An Inhibitor Of Wnt Signalingmentioning
confidence: 99%
“…Recently, the ubiquitin E3 ligase Smad ubiquitylation regulatory factor 1 (Smurf1) has been shown to modify Axin with nondegradable K29-linked ubiquitin polymers (Fei et al, 2013). K29-polyubiquitylation of Axin disrupts its interaction with the Wnt coreceptors LRP5 and LRP6 (LRP5/6), which subsequently attenuates Wnt-stimulated LRP6 phosphorylation and represses Wnt/β-catenin signaling (Fei et al, 2013). Interestingly, the OTU family DUB Trabid (also known in mammals as ZRANB1), which is a positive regulator of Wnt-induced transcription, shows a strong preference for K29 and K33 linkages (Kristariyanto et al, 2015a;Licchesi et al, 2012;Mevissen et al, 2013;Michel et al, 2015;Virdee et al, 2010).…”
Section: K29 Linkages -An Inhibitor Of Wnt Signalingmentioning
confidence: 99%
“…With the exception of substrate specificity, the specific ubiquitin chains also play regulatory roles in the biological functions of their modified protein substrates. Using an MS-based approach, Li Lin and his colleagues [55] demonstrated that Smurf1-mediated Lys29-linked polyubiquitination of axin negatively regulates Wnt/β-catenin signaling without proteolytic activity.…”
Section: Technology Development For Other Protein Ptmsmentioning
confidence: 99%